Didactical design of the proportionality concept based on anthropological theory of the didactic - Yugni Maudy, Septiani; Ruli, Redo Martila (Universitas Islam Negeri (UIN) Mataram, 2025)
[English]: This study aims to develop a didactic design grounded in the Anthropological Theory of the Didactic (ATD), with a focus on mathematical praxeology, to enhance students’ understanding of proportionality. The study uses the Didactical Design Research (DDR) methodology, which consists of three primary stages: retrospective analysis, metadidactical analysis, and prospective didactical situation analysis. Classroom observations, teacher and student interviews, and the examination of diagnostic tasks completed by thirty seventh-grade students at a junior high school in West Java, Indonesia, were used to gather data. The findings, which are interpreted using the Brousseau's framework, classify learning obstacles into three categories: (1) Ontogenic obstacles, which are associated with students' developmental readiness and prior knowledge; (2) Epistemological obstacles, which include misusing additive reasoning in multiplicative contexts and misinterpreting unit rates; and (3) Didactic obstacles, which are caused by unfamiliar task structures, implicit information, and insufficient instructional representations. The study has developed five learning tasks based on the praxeological framework, which included task, technique, technology, and theory. Despite not yet being used in classrooms, the didactic design's development is supported by both theoretical and empirical evidence. This study offers a different strategy for teachers dealing with proportionality learning obstacles and helps create more meaningful and contextually relevant math instruction. It also creates opportunities for further study to examine how the suggested design is implemented and how it affects students' mathematical thinking. [Bahasa]: Penelitian ini bertujuan untuk mengembangkan desain didaktik berbasis Teori Antropologi Didaktik (ATD) dengan fokus pada praksiologi matematika untuk membantu siswa agar lebih memahami konsep proporsionalitas. Metode yang digunakan adalah Didactical Design Research (DDR), yang terdiri dari tiga tahap utama: analisis retrospektif, analisis metadidaktik, dan analisis situasi didaktik prospektif. Data dikumpulkan melalui observasi di kelas, wawancara dengan guru dan siswa, serta analisis tugas diagnostik yang dikerjakan oleh 30 siswa kelas VII di sebuah SMP di Jawa Barat. Menggunakan kerangka Brousseau hasil penelitian ini menunjukkan bahwa hambatan belajar siswa terbagi menjadi tiga jenis: (1) hambatan ontogenik, yaitu terkait kesiapan dan pengetahuan awal siswa; (2) hambatan epistemologis, seperti penggunaan penalaran aditif yang salah dalam konteks yang seharusnya menggunakan penalaran multiplikatif, serta kesalahan dalam memahami laju satuan; dan (3) hambatan didaktik, yang muncul karena struktur tugas yang asing, informasi yang tidak jelas, serta kurangnya representasi yang memadai dalam pembelajaran. Berdasarkan temuan tersebut, dirancang lima tugas pembelajaran melalui pendekatan praksiologi. Studi ini memberikan alternatif strategi bagi guru untuk mengatasi kesulitan belajar proporsionalitas dan mendukung terciptanya pembelajaran matematika yang lebih bermakna dan relevan dengan konteks siswa. Selain itu, penelitian ini juga membuka peluang untuk penelitian lebih lanjut terkait penerapan desain ini dan dampaknya terhadap cara berpikir matematika siswa.